Environmental dynamism: the implications for operational and dynamic capabilities effects - Petrus, Barbara (Dynamizm otoczenia: implikacje dla efektów operacyjnych i dynamicznych zdolności, 2019)
The aim of this article is to recognize the implications of various types of environmental dynamism for the effects of operational and dynamical capabilities. The research method used is the critical analysis of literature in the field of strategic management. The research findings in the literature, on the operational effects and dynamic capabilities in the context of environmental dynamism were properly structured in the article. There were controversial research findings on environmental dynamism and its determining of the effects of operational and dynamic capabilities. The results indicate that operational and dynamic capabilities have different performance effects in high-dynamic and low-dynamic environments. The discussion on operational effects and dynamic capabilities in different market conditions still requires better theorizing and empirical research on the implications of market dynamism. The recommendations of the managers are directed at the understanding of the nature of the environment, which is crucial for the success of the implementation of new practices in the company.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 28-36
Keywords: environmental dynamism; dynamic capabilities; operational capabilities; competitive advantage; dynamizm otoczenia; zdolności dynamiczne; zdolności operacyjne; przewaga konkurencyjna